Oxidative and Antioxidative Stress Status in Children with Inflammatory Bowel Disease as a Result of a Chronic Inflammatory Process - Urszula Grzybowska-Chlebowczyk; Paulina Wysocka-Wojakiewicz; Martyna Jasielska; Bożena Cukrowska; Sabina Więcek; Maria Kniażewska; Jerzy Chudek (Mediators of Inflammation)
Oxidative stress (OS) has been recently implicated in the disease pathogenesis in inflammatory bowel disease (IBD). The aim of the study was to evaluate oxidative and antioxidative stress status and the risk of the atherosclerotic process in children with IBD and functional gastrointestinal disorders (FGID). The prospective study included a group of 71 children during a period of 2 years. In all children, laboratory tests were performed and intima-media complex in the carotid artery was measured (IMC). Low values of OS were more frequent in children with IBD than in the FGID group. The average concentration of oxidized lipoprotein with average density (oxLDL) was lower in patients with IBD. Among patients with IBD, higher concentrations of oxLDL were recorded in patients with longer-duration disease and with higher concentrations of total cholesterol. In the IBD group, more often, higher concentrations of anti-oxLDL were recorded among patients with longer-duration disease. The obtained results did not support the hypothesis of total antioxidant capacity depletion and greater overall OS in patients with IBD. Patients with IBD with a longer duration of the disease have higher concentrations of oxLDL and anti-oxLDL.